Environmental concerns and agricultural trade: Building a responsible and effective relationship - Papendieck, Sabine; McNamara, Brian (International Food Policy Research Institute, 2024)
The rapid expansion of goods and services trade over the last several decades has created complex interdependencies between production, consumption, and job creation across economies. At the same time, a range of environmental issues-declining biodiversity, water scarcity, and water pollution, as well as climate change-are becoming more acute and call for strong, immediate, and coordinated international action. Countries and companies around the world are making ambitious climate change mitigation plans to address the climate crisis and to reach the net-zero emissions global target determined at the Paris Agreement. In this context, addressing the nexus between international trade and sustainable development is now more urgent than ever.